Serum phosphate is associated with mortality among patients admitted to ICU for acute pancreatitis. Issue 5 (5th May 2021) - Hedjoudje, Abdellah; Farha, Jad; Cheurfa, Chérifa; Grabar, Sophie; Weiss, Emmanuel; Badurdeen, Dilhana; Kumbhari, Vivek; Prat, Frédéric; Levy, Philippe; Piton, Gaël
Abstract: Background and Aims: Routine laboratory tests can be useful predictors in the early assessment of the severity and mortality of acute pancreatitis (AP). The aim of this study was to evaluate the accuracy of clinical and laboratory parameters for the prediction of mortality among patients admitted to the intensive care unit (ICU) for AP. Methods: We conducted a retrospective analysis of prospectively collected data from Beth Israel Deaconess Hospital made publicly available to examine the relationship between routine clinical and laboratory parameters with respect to mortality for AP. Cox proportional hazard ratio was used to evaluate the impact of several routine laboratory markers on mortality. Receiver operation characteristic (ROC) curve was performed to determine the accuracy of diagnosis of laboratory tests by using area under curve (AUC) for the respective analysis. Results: In total, 499 patients were admitted to the ICU for AP. Several factors for predicting mortality in AP at admission were identified in the multivariate analysis: alkaline phosphatase hazard ratio (HR) = 1.00 (1.00–1.00, p  = 0.024), anion gap HR = 1.09 (1.00–1.20, p  = 0.047), bilirubin total HR = 1.11 (1.06–1.17, p  < 0.001), calcium total HR = 0.59 (0.42–0.84, p  = 0.004), phosphate HR = 1.51 (1.18–1.94, p  = 0.001), potassium HR = 1.91 (1.03–3.55, p  = 0.041), white blood cells HR = 1.04 (1.00–1.07, p  = 0.028). The AUC of serum phosphate level for mortality was 0.7 in the ROC analysis. The optimal cut‐off value of serum phosphate level for prediction of mortality was 3.78 mg/dl (sensitivity, 0.58; specificity, 0.78). Conclusion: In this large cohort, we identified baseline serum phosphate as the most valuable single routine laboratory test for predicting mortality in AP. Future prospective studies are required to confirm these results. Key Points: This is the first study that evaluates the role of serum phosphate at baseline for predicting the mortality of acute pancreatitis (AP) in intensive care unit (ICU). This study found that serum phosphate is a useful laboratory marker for predicting the mortality of AP independently of other known factors. This study found that serum phosphate value greater than 3.78 mg/dl within the first 24 h after admission in the ICU could predict mortality (area under curve = 0.7, p  < 0.001, sensitivity 58%; specificity 77%).